(untitled) (Journal of Parents and Teachers, 2025)
Integrating theater into education not only enriches students’ artistic expression, but also strengthens skills such as empathy, communication, and teamwork. By adopting practices that combine education and art, teachers not only revitalize their own passion and creativity, but also create an environment where students feel safe to explore and express their ideas. The classroom becomes a dynamic and collaborative learning space, where every voice is valued and imagination becomes a powerful tool for both academic and personal growth.